Evaluation of SeaWiFS and MODIS chlorophyll-a products in the Argentinean Patagonian Continental Shelf (38º S - 55º S) - Dogliotti, Ana Inés (2009)
Field measurements of surface chlorophyll-a concentration were used to evaluate for the first time the performance of the standard Moderate Resolution Imaging Spectroradiometer (MODIS) and both standard and regional Sea-viewing Wide Field-of-view Sensor (SeaWiFS) ocean colour algorithms in the Patagonian Continental Shelf (PCS) between 38u S and 55u S. The results showed that the regional algorithms did not significantly improve the global algorithm estimates. Moreover, the SeaWiFS OC4v4 algorithm, National Aeronautics and Space Administration (NASA) standard chlorophyll product, showed the best performance among all the algorithms examined. Nonetheless, all the global and local algorithms analysed showed uncertainties dependent on chlorophyll concentration. Low chlorophyll-a concentration values tended to be overestimated and high values tended to be underestimated. A regional analysis within the PCS showed that higher uncertainties are found in the homogeneous side of the tidal fronts present in the PCS, in areas suggested to be optically complex case 2 waters, while a better result (less bias) was obtained in the southern mid-shelf region. We discuss the probable reasons and provide possible explanations of the regional differences in the performance of the algorithms.